A renewed search for meaning? - Stensaker, Bjørn (Högre utbildning, 2020)
Book review: The responsible university – exploring the Nordic context and beyond (2019). Sørensen, Mads, Geschwind, Lars, Kekäle, Juoni & Pinheiro, Rómulo (Eds.) PalgraveMacmillan (Open access). https://10.1007/978-3-030-25646-3